Peningkatan Kemampuan Menulis Cerpen melalui Pengalaman Pribadi Siswa Kelas VIII SMP UNISMUH Makassar - Indramini Indramini (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
"Improvement of Short Story Writing Ability Through the Personal Experience of Class VIII Unismuh Junior High School Makassar". Thesis of Indonesian Language and Literature Education Department, Faculty of Teacher Training and Education, Makassar Muhammadiyah University.This type of research is a Class Action Research (Class Action Research) which aims to describe the improvement of short story writing skills through the personal experience of students of class Class VIII Unismuh Junior High School Makassar and describes the process of improving the ability to write short stories through the personal experience of the MA class Class VIII Unismuh Junior High School Makassar. The instruments used in data collection were tests, observation guidelines, interview guidelines, and the data were analyzed descriptively qualitatively. The data in this study are in the form of tesp there are 24 students and the results of observations in the learning process.The results showed that quantitatively there was an increase in the learning outcomes of short story writing through the personal experience of 24 students, namely on the pretest results, an average score of 56.63%. In the first cycle the average score of student learning outcomes was 68.13%, while the second cycle of student learning outcomes writing short stories through personal experience was 81.74%. In the first cycle, students who finished 9 students or 46.48% and categories of incomplete were 15 students or 53.52%. While in the second cycle category there were 21 students or 89.96% and the incomplete category were 3 people or 10.04% meaning that there was an increase of 13.61%.Based on the results of the research above, it can be concluded that the results of learning to write short stories through the personal experience of students of class XI MA Darul Istiqamah Maccopa Maros Regency can be improved through students' personal experiences.